Small non-coding RNA profiling in patients with non-muscle invasive bladder cancer - Jiajia Cai; Zeqin Yan; Yadi Zhong; Yuqing Li; Jianxu Huang; Huijuan Hu; Yingrui Li; Hu Fang; Song Wu (BMC Cancer)
Abstract The intricate regulatory roles of small non-coding RNAs (sncRNAs), including PIWI-interacting RNAs (piRNAs) and microRNAs (miRNAs), have been increasingly recognized in the modulation of cellular functions and are associated with the pathogenesis of various diseases, notably cancer. However, the specific dysregulation patterns of sncRNAs in non-muscle-invasive bladder cancer (NMIBC) have yet to be fully delineated, highlighting a significant gap in our current understanding. To elucidate the expressional dynamics of sncRNAs for patients with NMIBC, we characterized the profile of piRNAs and miRNAs by next-generation sequencing. We identified the differentially expressed sncRNAs between tumor and paracancerous tissues and characterized their distribution along the genome. We further revealed a set of immune-related piRNAs and dysregulated miRNAs that might be associated with NMIBC pathogenesis. Differentially expressed piRNAs were predominantly localized at the long arms of chromosomes 13, 1, and 6. Notably, the targets of specific piRNAs, including piR-hsa-2215234, piR-hsa-105306, piR-hsa-102066, and piR-hsa-236465, show significant associated with antigen processing and presentation pathway. Additionally, differentially expressed miRNAs are mainly located on chromosome 14 and their target genes tend to be involved in cancer-related pathways, suggesting their potential regulatory roles in NMIBC. Collectively, this study revealed the global sncRNA dysregulation in NMIBC, and the identified sncRNAs are implicated in the modulation of both immune and cancer pathways, suggesting their contribution to the pathogenesis and potential targets for immunotherapy.